G01 Quantifying the traverse: a comprehensive kinematic analysis of climbing technique - Andrews-Cifre, Joseph; Bailey, Simon; Taylor, Nicola (Graduate Journal of Sports Science, Coaching, Management, & Rehabilitation, 2024)
Biomechanical analysis plays a pivotal role in enhancing performance and preventing injuries in rock climbing. Despite a recent increase in popularity, there remains a lack of research quantifying full-body movements, resulting in uncertainty regarding biomechanical demands and variability. It should be noted that there is a scarcity of data in climbing research to quantify optimal techniques, particularly for traverses. This study aims to address this gap by examining the demands of a traverse in a controlled setting using Vicon marker-based three-dimensional (3D) motion capture. Fourteen experienced climbers (32 ± 13 years, 70 ± 9 kg) with varying skill levels (intermediate to advanced) and climbing backgrounds (sport climbing, trad climbing and bouldering) completed a two-minute standardised traverse on a custom-built Lattice circuit (2440 × 2440 × 1220 mm). A twelve-camera (200 Hz, Vantage) motion analysis system (Vicon, Motion Systems Ltd. Oxford, United Kingdom) acquired kinematic data. Retroreflective markers were attached to anatomical landmarks of the upper and lower body. The trials were preceded by a 10-minute self-selected warmup. This data will be analysed to assess the degree of inter-participant variability, observing if there is the possibility of quantifying an optimal traversing technique. Intra-participant variability will be assessed, to measure the effect of fatigue on the climbing movement. Previous literature has alluded to the possibility of fatigue increasing the use of the legs when climbing as compensation. Comparing the beginning of the traverse to the end, data should further substantiate this claim. This research will offer insights into the kinematic demands of rock climbing, laying the groundwork for further studies on a larger scale to assess the possibility of optimising technique, performance, and injury strategies. This study contributes to bridging the vast gap between biomechanical research and practical applications in the climbing community, facilitating a more evidence-based approach to performance.